Biosynthesis, Characterization and Bioactivity of Selenium Nanoparticles Synthesized by Propolis: 1Ahmed Thamer Wali1 and 2Majida A. J. Alqayim - Wali, Ahmed Thamer (The Iraqi Journal of Veterinary Medicine, 2019)
Biosynthesis of selenium nanoparticles is safe, inexpensive, eco-friendly, non-toxic materials, furthermore, is more stable due to natural coating of the organic molecules and do not aggregate with time, here by the present study designed to investigate the bioactivity and safety of a new biogenic Selenium- nanoparticles using synthesized by propolis. To evaluate biogenic Selenium-nanoparticles, 27 adult rats were divided in to 3 groups: first group consider as control(C), seconed group (T1) received inorganic selenium by orally administration in a dosage of 100μg /kg BW third group (T2) received Selenium nanoparticles orally in a dosage 100μg /kg BW for 4 weeks. Body weight, food intake, blood Selenium binding protein, Catalase, and liver enzymes Aspartate Amino Transferase and Alanin Amino transferase were evaluated two weeks interval. Results showed that body weight and food intake were elevated significantly during the experiment periods. Rats had selenium nanoparticles showed significant increase in Selenium binding protein and Catalase correlated with normal values of liver enzymes. It can be concluded that the new propolis mediated Selenium- nanoparticles improve the availability of the Selenium to its binding proteins that limit its toxicity when compare with inorganic selenite.